The Corporate Governance of Banks: A Concise Discussion of Concepts and Evidence - Levine, Ross (World Bank, Washington, D.C., 2013)
The author examines the corporate governance of banks. When banks efficiently mobilize and allocate funds, this lowers the cost of capital to firms, boosts capital formation, and stimulates productivity growth. So, weak governance of banks reverberates throughout the economy with negative ramifications for economic development. After reviewing the major governance concepts for corporations in general, the author discusses two special attributes of banks that make them special in practice: greater opaqueness than other industries and greater government regulation. These attributes weaken many traditional governance mechanisms. Next, he reviews emerging evidence on which government policies enhance the governance of banks and draws tentative policy lessons. In sum, existing work suggests that it is important to strengthen the ability and incentives of private investors to exert governance over banks rather than to rely excessively on government regulators. These conclusions, however, are particularly tentative because more research is needed on how legal, regulatory, and supervisory policies influence the governance of banks.